2014
DOI: 10.1186/1475-2859-13-24
|View full text |Cite
|
Sign up to set email alerts
|

A marine sponge associated strain of Bacillus subtilis and other marine bacteria can produce anticholinesterase compounds

Abstract: BackgroundAcetylcholinesterase (AChE) inhibitors or anticholinesterases reduce the activity of enzyme acetylcholinesterase that degrades the neurotransmitter acetylcholine in the brain. The inhibitors have a significant pharmacological role in neurodegenerative diseases like Alzheimer’s and Parkinson’s etc. Although plants have been a significant source of these compounds, there are very few sporadic reports of microorganisms producing such inhibitors. Anticholinesterase activity in bacterial associates of mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…collected from Kanyakumari coast [17]. Two potential biosurfactants producing strains such as Bacillus subtilis and Bacillus amyloliquefaciens were reported as sponge associated bacteria from C. diffusa collected from Kanyakumari coast reported that B. subtilis associated with marine sponge can produce anticholinesterase compounds [18,19]. The Bacillus subtilis VCDA isolated from C. diffusa possessed inhibitory activity against E. coli (10 mm), S. aureus (16 mm), Proteus vulgaris (9 mm), Vibrio fluvialis (11 mm) which correlate with the reports of B. cereus SBSO 2 isolated from sponge Hyatella cribriformis that showed activity 12 mm for S. aureus, 11 mm for S. typhii, 7 mm against P. mirabilis and Vibrio cholerae (10 mm).…”
Section: Discussionmentioning
confidence: 99%
“…collected from Kanyakumari coast [17]. Two potential biosurfactants producing strains such as Bacillus subtilis and Bacillus amyloliquefaciens were reported as sponge associated bacteria from C. diffusa collected from Kanyakumari coast reported that B. subtilis associated with marine sponge can produce anticholinesterase compounds [18,19]. The Bacillus subtilis VCDA isolated from C. diffusa possessed inhibitory activity against E. coli (10 mm), S. aureus (16 mm), Proteus vulgaris (9 mm), Vibrio fluvialis (11 mm) which correlate with the reports of B. cereus SBSO 2 isolated from sponge Hyatella cribriformis that showed activity 12 mm for S. aureus, 11 mm for S. typhii, 7 mm against P. mirabilis and Vibrio cholerae (10 mm).…”
Section: Discussionmentioning
confidence: 99%
“…Based on its phenotypic properties and 16S rDNA sequencing, the strain was identified as Bacillus subtilis . This result showed that acetylcholinesterase inhibitors are quite common found in marine bacteria [ 102 ].…”
Section: Neuropeptides From Marine Sourcesmentioning
confidence: 99%
“…Additionally, from the metabolites of Actinobacillus N98-1021, Dong et al [ 56 ] isolated the compound N98-1021A, which exhibits the AchEI activity using the modified Ellman’s method and shows structural similarity to terferol. Moreover, Pandey et al [ 50 ] extracted a Bacillus subtilis strain-M18SP4P from Fasciospongia cavernosa and showed that this strain blocks 54% of acetylcholinesterase activity. Using galanthamine as a positive reference, TLC bioautography identified two components in the metabolites of M18SP4P with the AchEI activity.…”
Section: Types Of Acheis Produced By Microbesmentioning
confidence: 99%